DEVELOPMENT AND EVALUATION OF A WEB-BASED SALES AND MARKETING INFORMATION SYSTEM TO IMPROVE TRANSACTION AND PROMOTION EFFICIENCY: A CASE STUDY OF SALSA BAKERY - Mita Yuliana; Rita Irviani (YHMM PUBLISHING, 2025)
This study aims to develop and evaluate a web-based sales and digital marketing information system to improve transaction efficiency and promotional effectiveness at Salsa Bakery, a small-scale enterprise in the food and beverage sector. The existing system relied on conventional methods, where transactions and data recording were conducted manually, leading to inefficiencies, data inaccuracies, and limited marketing reach. To address these issues, a web mobile-based system was designed using the Waterfall development method and modeled with Unified Modeling Language (UML). Data collection techniques included observation, interviews, and literature study to ensure system requirements aligned with real business needs. The system was evaluated using a simple statistical approach involving 3 staff members and 30 customers. The results indicate significant improvements in transaction efficiency, promotional effectiveness, customer satisfaction, and staff performance. The system enables real-time product information access, faster transaction processing, and broader digital promotion through an integrated platform. The findings demonstrate that implementing a web-based sales and marketing system can effectively support digital transformation in small and medium enterprises (SMEs). This study contributes to the development of practical solutions that enhance operational performance and competitiveness, particularly in the bakery industry.